Developmental landscape of computational techniques to explore the potential phytochemicals from Punica granatum peels for their antioxidant activity in Alzheimer’s disease - Parveen, Shagufta; Batool, Aneeqa; Shafiq, Nusrat; Rashid, Maryam; Sultan, Ayesha; Wondmie, Gezahign Fentahun; Bin Jardan, Yousef A.; Brogi, Simone; Bourhia, Mohammed (Frontiers in Molecular Biosciences, 2023)
Alzheimer's disease (AD) is most commonly found in women than men as the risk increases with age. Phytochemicals are in-silico screening from Punica granatum peels for their antioxidant activity to utilized for Alzheimer's disease. Alzheimer's disease is inhibited by the hormone estrogen which protect the brain from the bad effect of amyloid-beta and Acetylcholine (ACh), and is important for memory processing. For the purpose, a library of about 1000 compounds from Punica granatum were prepared and studied by applying integrated computational calculations like 3D-QSAR, Molecular docking, MD simulation, ADMET and DFT. The 3D-QSAR model screened the active compounds B25, B29, B35, B40, B45, B46, B48, B61, and B66 by the field points and activity atlas model from prepared library. At the molecular level, docking was performed on active compounds for leading hit compounds as B25 and B35 that displayed a high MolDock score, efficacy and compatibility with drug delivery against the antioxidant activity. The optimization of the structure and chemical reactivity parameter of the hit compound was calculated by density functional theory (DFT). Moreover, ADMET prediction was evaluated to check the bioavailability and toxicity of the hit compound. Hesperidin (B25) is hit compound after whole study and can synthesize for potent drug discovery in future.